Authority Of The Consumer Dispute Resolution Agency (Bpsk) In Disputes Between Doctors And Patients Who Provide Illegal Drugs - sinergilp, Andreas Henfri Situngkir; Fauzan (International Journal of Synergy in Law, Criminal, and Justice, 2024)
The provision of quality health services is a fundamental right for everyone. However, in practice, disputes often occur between doctors and patients, one of which is related to the administration of illegal drugs. This research aims to analyze BPSK's authority in resolving disputes between doctors and patients who prescribe illegal drugs. This study employs normative juridical methods. The data collection is conducted through literature review. Once collected, the data is analyzed in three stages: data reduction, data presentation, and drawing conclusions. The research results show that BPSK plays a role as a mediation, arbitration and conciliation institution whose function is to provide protection to consumers. BPSK has the authority to assess whether doctors have violated consumer rights by providing drugs that do not meet safety and legality standards. In addition, BPSK can provide decisions that are binding on both parties. This authority includes enforcing consumer protection laws, resolving disputes fairly, and restoring the rights of aggrieved consumers.